AXOPLASMIC TRANSPORT IN THE CRAYFISH NERVE CORD : The Role of Fibrillar Constituents of Neurons - Fernandez, H. L. (The Rockefeller University Press, 1971)
(a) Axoplasmic transport of tritium-labeled proteins in crayfish nerve cord was confirmed at a slow rate of 1 mm/day. A second proteinaceous component which moves at a rate of 10 mm/day was also detected. Radioautography and biochemical analysis indicate that proteins migrating at these velocities have a perikaryal origin and move caudad within axons as sharply defined peaks. (b) Evidence is presented for the blockage of the slow and the fast movement of proteins by intraganglionic injection of the anti-mitotic agent vinblastine sulfate (0.1 mM). (c) Electron microscope observations of vinblastine-treated ganglia revealed a reduction in the number of axonal microtubules and the formation of intracellular aggregates presumably composed of microtubular protein. (d) These findings would be compatible with the involvement of microtubules in both slow and fast axoplasmic transport. However, the block induced by vinblastine was detected in regions of the cord (up to 10 mm away from the injection site) where the number and morphology of microtubules appeared unaltered. In addition, axons showing effects of vinblastine occasionally contained mitochondria with remarkably dense and thickened membranes. (e) In association with the surfaces of axonal microtubules are lateral filamentous elements (40–80 A in diameter) which also showed vinblastine-induced alterations. Our observations indicate that such filiform structures, associated with microtubules, may be a necessary component in the transport mechanism(s).